THE DEVELOPMENT OF A TEST SOFTWARE SUITE FOR FLIGHT CONTROL LAWS EVALUATION OF THE LSA-02 UAV TECHNOLOGY DEMONSTRATOR - Mohd Ichwanul Hakim, Teuku
Flight Control Laws (FCL) for Basic Electronic Flight Control System (BEFCS) of LSA-02 UAV technology demonstrator has been developed. The FCL has full authority to control the aircraft in all axes. The FCL needs to be evaluated before it is implemented into the aircraft. The evaluation of the FCL is very stringent process. Safety and performance requirements shall be met in any flight condition. Evaluation tool and method shall be developed to allow testing of the FCL in a wide range of flight envelope for both normal and under disturbed conditions.